Mashi Baker's / Nur Athirah Syazana Suhaimi and Siti Ghufairatul Athirah Mohamed Rahim - Suhaimi, Nur Athirah Syazana; Mohamed Rahim, Siti Ghufairatul Athirah (2022)
Mashi Baker's is a tiny firm that relies on its own resources or profits to grow. It sells its goods via an internet platform. The major goals of Mashi Baker's are to promote people to enjoy and buy their cakes as well as to establish a well-known business in Sungai petani regions, Kedah.